2020
DOI: 10.1016/j.heliyon.2020.e05650
|View full text |Cite
|
Sign up to set email alerts
|

Masculine norms and mental health of African men: what can psychology do?

Abstract: In Africa, internalisation of masculine norms among men has been reported to make them more susceptible to mental health problems. In this chapter, social construction and role theories are used to explore the relationships between masculine norms and mental health among men in Africa. The authors argued that due to traditional and institutionalised beliefs, men engage in restrictive emotionality through defence mechanisms by denying their mental health challenges and status. Hence, an inclusive model of remed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 54 publications
4
16
0
Order By: Relevance
“…These findings are supported by those of Ezeugwu and Ojedokun (2020) who found that mental health was mainly sidelined in support of adverse effects of communicable and infectious diseases such as malaria. In the health system, mental health was placed at the lower ranks of the health hierarchy.…”
Section: One Of the Key Informants Indicated;supporting
confidence: 74%
See 1 more Smart Citation
“…These findings are supported by those of Ezeugwu and Ojedokun (2020) who found that mental health was mainly sidelined in support of adverse effects of communicable and infectious diseases such as malaria. In the health system, mental health was placed at the lower ranks of the health hierarchy.…”
Section: One Of the Key Informants Indicated;supporting
confidence: 74%
“…In Africa, mental health issues have received limited attention from policymakers and governments. Ezeugwu and Ojedokun (2020) assert that Africa's focus on the adverse effects of communicable and infectious diseases, malnutrition and low incomes has sidelined the focus on mental health. As a result, mental health is placed at the lower ranks of the health hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of our study population were young males in their third and fourth decades of life, which contrasts with several other studies where more female donors were encountered with a mean age of over 50 years [ 16 , 17 ]. This is likely due to the fact that most Africans believe that men are stronger than their female counterparts, and hence able to withstand the rigors of surgery [ 18 ]. In our center, DNs were performed 2.5 times more on the left than on the right side; this finding is similar to reports in several other international studies [ 4 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…When fathers express distress over the increasing cost of goods and food insecurity, they are also aware of government policies and environmental stressors that trigger and/or exarcebate these situations. In the Ghanaian setting, where providing material resources for one’s family ( Coe, 2011 ; Ezeugwu & Ojedokun, 2020 ) is synonymous with being a “good” husband and provider, these exacerbating factors may leave men feeling powerless and out of control in their roles as fathers; prompting behavioral or emotional exhaustion, and decreasing their psychological wellbeing ( Amarachi et al, 2020 ; Kaya et al, 2019 ).Within the qualitative accounts, psychological stress was prevalent and is consistent with emerging data suggesting fatherhood can negatively impact paternal mental health. A 2010 U.K.-based study concluded that 21% of fathers experienced depression by the time their children were 12 years old ( Davé et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Fast et al examining masculine idealogies in Tanzania and Kenya, the authors reported increased rates of depression and suicidality among men who were unable to fulfill their expected roles and responsibilities as “financial providers” ( Fast et al, 2020 ). These men, the authors posit, experienced prolonged periods of depression, anxiety, and stress, which had been entrenched and deepened by economic, political, and social uncertainty; before succumbing to taking their own lives to avoid the shame of being “too poor to provide for their families.” Even though there are changes in the fatherhood role in the new African dual-earner families, an adult male is still considered a husband (e.g., with one wife or more), a father (with or without children), an uncle (with responsibilities to others within the extended families), an employee or a manager (fulfilling their job role to the organization), and can also occupy a city or village chieftaincy position within their age grade ( Ezeugwu & Ojedokun, 2020 ; Kelly, 2018 ). The pressures placed on African men can seem insurmountable and yet an overarching theme that emerged from our study was the sense of pride and joy that fatherhood brings to these men, counter-balancing the stress-related findings.…”
Section: Discussionmentioning
confidence: 99%